2021
DOI: 10.1371/journal.pone.0245999
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Covid-19-related distress on general health, oral behaviour, psychosocial features, disability and pain intensity in a cohort of Italian patients with temporomandibular disorders

Abstract: This study aimed to understand the impact of COVID-19 distress on psychological status, features of central sensitization and facial pain severity in people with temporomandibular disorders (TMDs). In this prospective cohort study, 45 adults (19 chronic, 26 acute/subacute TMD) were recruited prior to the COVID-19 outbreak. Baseline assessment took place before the outbreak while a follow-up was performed immediately after the lockdown period. Multiple variables were investigated including age, gender, perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 60 publications
1
40
0
3
Order By: Relevance
“…Dos artigos incluídos nesta revisão, 7 abordavam aspectos psicossociais e sua relação com a pandemia por COVID-19 (Di Blasi et al, 2021;De Boni et al, 2020;Gutiérrez-Hernández et al, 2021;Limcaoco et al, 2020;Liao et al, 2021;Liu et al, 2021;Wang et al, 2021), 5 apresentavam os aspectos psicossociais e sua relação com DTM (Alahmary, 2019;Guimarães;Almeida, 2018;Canales et al, 2019;Yap;Natu, 2020;Zavanelli, 2017) e 7 dissertavam sobre a associação entre as alterações psicológicas causadas pela pandemia por COVID-19 e sua relação com bruxismo e DTM (Asquini et al, 2021;Emodi-Perlman et al, 2020;Gaş;Özsoy;Aydin, 2021;Medeiros et al, 2020;Restrepo et al, 2021;Saccomanno et al, 2020;Silva et al 2021).…”
Section: Discussionunclassified
“…Dos artigos incluídos nesta revisão, 7 abordavam aspectos psicossociais e sua relação com a pandemia por COVID-19 (Di Blasi et al, 2021;De Boni et al, 2020;Gutiérrez-Hernández et al, 2021;Limcaoco et al, 2020;Liao et al, 2021;Liu et al, 2021;Wang et al, 2021), 5 apresentavam os aspectos psicossociais e sua relação com DTM (Alahmary, 2019;Guimarães;Almeida, 2018;Canales et al, 2019;Yap;Natu, 2020;Zavanelli, 2017) e 7 dissertavam sobre a associação entre as alterações psicológicas causadas pela pandemia por COVID-19 e sua relação com bruxismo e DTM (Asquini et al, 2021;Emodi-Perlman et al, 2020;Gaş;Özsoy;Aydin, 2021;Medeiros et al, 2020;Restrepo et al, 2021;Saccomanno et al, 2020;Silva et al 2021).…”
Section: Discussionunclassified
“…Studies by List et al demonstrated that 15% of adults and 7% of adolescents were affected by the condition [ 5 ], contrary to Valesan et al who reported TMD prevalence at 31% in the population of adults/the elderly and 11% in children/teenagers [ 6 ]. These disorders affect the whole adult population but the highest number of diagnosed cases is reported in the 20–40 years age range [ 1 , 5 , 7 , 8 , 9 , 10 ]. At the same time, women are reported to be more often affected by masticatory dysfunctions than men.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, women are reported to be more often affected by masticatory dysfunctions than men. Women are two-to-four times more likely to experience pain due to masticatory activities than men [ 1 , 2 , 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Besides a high incidence of TMJ and/or muscle dysfunctions in women, they also suffer from a wider range of symptoms and their increased intensity [ 14 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations